2010
DOI: 10.1002/pbc.22918
|View full text |Cite
|
Sign up to set email alerts
|

Sex cord stromal tumors of the ovary in children: A clinicopathological report from the Italian TREP project

Abstract: Completeness of resection and histology were important prognostic factors; in our series the Sertoli-Leydig Cell tumor was the most aggressive variety. Hormonal signs (precocious puberty, telarca, menarche) were common in younger patients and led to an early diagnosis. Cisplatin based chemotherapy seemed to be effective for locally advanced tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 34 publications
4
42
0
1
Order By: Relevance
“…This is in accordance with the available international literature. [6][7][8][9] The histomorphological observations in our study are similar to other reports. 6,7 We observed that most of the tumors were unilateral, ranging from 5 to 15 cm in size.…”
Section: Resultssupporting
confidence: 91%
“…This is in accordance with the available international literature. [6][7][8][9] The histomorphological observations in our study are similar to other reports. 6,7 We observed that most of the tumors were unilateral, ranging from 5 to 15 cm in size.…”
Section: Resultssupporting
confidence: 91%
“…Only one SST and two Fibromas were encountered in premenstrual females. In post pubertal patients, 9 cases each of JGCT and SST were found as depicted in Table 2, while in literature Sertoli Leydig cell tumour are more common in this group Cecchetto et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In most of previous studies reported, fibrothecoma group comprised of one of common neoplasms among SCST in younger age, we also had 10 cases of tumours of this spectrum, and all of these behaved as benign tumours (Cecchetto et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They rarely occur in childhood and adolescence [1,2,3]. In about 40% of cases, they show an autonomous testosterone production which causes virilization [7]. After clinical examination and serum hormone measurement, radiographic imaging plays an important diagnostic role.…”
Section: Discussionmentioning
confidence: 99%